River Scenery, Trinidad, B.W.I. - (:unkn) unknown (Muir Marshall and Co.[Trinidad and Tobago], 2011)
The postcard shows an idyllic river scene. Postcard number i 16059.
Colour: Black and white; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Rivers--Trinidad and Tobago; Bamboo--Trinidad and Tobago; [1910]; Plants--Trinidad and Tobago; Rocks--Trinidad and Tobago; Boulders--Trinidad and Tobago; Scenic byways--Trinidad and Tobago; Scenes--Trinidad and Tobago; Landscapes--Trinidad and Tobago